Effect Of Magnesium And Tin As Sintering Additives On Microstructure And Compressive Properties Of Porous Aluminum - Ahmad Hamdi, Amirah (2018)
The main objective of this research was to improve the compressive properties of porous aluminum by addition of sintering additives; magnesium (Mg) and tin (Sn). Addition of Mg with Sn enhance sintering response of porous Al via liquid phase mechanism. Porous Al were fabricated by powder metallurgy method using carbamide as space holder. The process begin by varies the amounts of carbamide (20 wt.%, 40 wt.% and 60 wt.%) in porous Al-1.0Mg. Then after achieving the best composition of carbamide with desired properties, amount of Mg was varied (0.2, 0.6, 1.0, 1.2 and 1.6 wt.%). The process then followed by varying the amounts of Sn (0.2, 0.6, 1.0, 1.2, 1.6, 2.0, 2.4, 3.0 and 4.0 wt.%) in porous Al-1.0Mg. Characterization such as microstructure, morphology, phases, density, porosity and compressive strength were done using optical microscope (OM), scanning electron microscope (SEM), X-ray Diffractometer (XRD), density and porosity test and compression test. It was found that porous Al-1.0Mg has porosities in the range of 36.0% to 75.4% with density ranges from 1.75 to 0.67 g/cm3 with additions of carbamide from 20 wt.% to 60 wt.%. Porous structure was obtained with the removal of carbamide through dissolution process. The addition of 1.0 wt.% Mg was able to achieve compressive strength of 4.20 MPa and energy absorption of (7.35 MJ/m3). Whereas, porous Al-1.0Mg-2.4Sn has produced the highest compressive strength (17.72 MPa) and the highest energy absorption (8.67 MJ/m3).